Application of the Composting Method as an Emergency Measure for Household Organic Waste Management - Yanuar Sinatra; Amritha Suko Zaqinadevi; Akhmad Sidiq; Azhar Arkho (GUYUB: Journal of Community Engagement, 2025)
As a tourist destination, Kota Batu must prioritize environmental cleanliness, aesthetics, and urban management in its development. However, the waste management system, which previously functioned well, has significantly deteriorated, leading to a waste emergency. As a result, residents struggle to dispose of household waste as they did before. Initially, waste disposal was done independently, but now the community is required to manage their waste without adequate knowledge. This situation has led to irregular household waste disposal practices. As part of community service efforts, this study applies the composting method as an emergency solution for household organic waste management in Junrejo Village, Junrejo District, Kota Batu. This method is expected not only to address the waste emergency but also to serve as a reference for other regions facing similar challenges. The outcomes of this initiative include the creation of a sample landfill for organic waste management and community education on composting applications. It is hoped that this program can be expanded on a larger scale and serve as a model for community-based waste management. Consequently, this initiative contributes to raising public awareness of the importance of sustainable waste management while supporting the cleanliness and beauty of Kota Batu as a leading tourist destination